MULTI-CRITERIA DECISION MODEL FOR MATERIAL SUPPLIER SELECTION FLEXIBLE PAVEMENT USING THE ANALYTICAL HIERARCHY PROCESS (AHP) METHOD - Rizkian, Alhanza; Jumas, Dwifitra Y; Rita, Eva (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
This research was conducted on construction workers / contractors in the field of roads and bridges in the province of West Sumatra. This study aims to provide consideration for construction companies in choosing the right supplier by considering various criteria, determine the priority scale of supplier selection activities for construction actors/contractors, provide suggestions or solutions for selecting flexible pavement suppliers for construction actors in the province of West Sumatra by using the Analytic Hierarchy Process (AHP) method. The results showed that the criteria and sub-criteria can be used as suggestions or solutions, namely supplier profiles consisting of certificates and business licenses, not blacklisted, clear company name and address, capital, company age, performance over the last 5 years and this year, total and quality of employees, and the number of clients in a year safety records consist of taking materials with eco-friendly designations, availability of training for new employees, the importance of applying OSH in the work environment, and the number of accidents in the last 5 years and delivery consisting of timely delivery, delivery distance, delivery of materials according to the order, and the type and amount of shipping transportation. With the supplier profile factor weighing 49.70% safety record factor 21.90% delivery factor 11.70% quality factor 6.80% cost factor 5.80% service factor 4.10%.